PENERAPAN DIVERSI TERHADAP ABH DALAM SPP DI WILAYAH HUKUM POLRES LIMAPULUH KOTA - Ana Ramadhona (Ensiklopedia Social Review, 2019)
Children are potential human resources and successors of the ideals of the nation's struggle. Protection of children must be carried out by all elements of the country. The existence of criminal acts committed by children is often criticized by law enforcement officers, because it is considered not to heed the procedures for handling children who have legal problems and seem to be treated as small adults who commit criminal acts. This study aims to find out and analyze the application of diversion to children dealing with law in the criminal justice system in the legal area of the Fifty City Police Resort, to find out and analyze the obstacles that arise in the application of diversion to children dealing with laws in the criminal justice system in the jurisdiction of the Fifty City Resort Police, and to know and analyze efforts in overcoming obstacles in the application of diversion to children facing the law in the criminal justice system in the legal area of the Fifty Cities Police Resort. The method used in this study is an empirical juridical approach. The Lima Puluh Kota Resort Police have implemented it well but not maximally because of the obstacles such as the many legalistic law enforcers, stiffness, and lack of understanding of the handling of Children Against the Law, the prosecutor's office has not received if the child is returned to his parents , the victims who did not want to forgive the perpetrators because of the large losses suffered by the victims. The negative paradigm of the community towards law enforcement had a major influence on the application of Diversion. Efforts made to overcome these obstacles are as optimal as possible the diversion reached an agreement between the victims and the perpetrators so that the rights of the Children facing the law (ABH) can be protected and investigators can seek the best for the interests of the child.